2022
DOI: 10.3389/fpls.2022.903272
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Arabidopsis N-Acetylglucosamine-1-P Uridylyltransferase Expression Impairs Protein N-Glycosylation and Induces ABA-Mediated Salt Sensitivity During Seed Germination and Early Seedling Development

Abstract: N-acetylglucosamine (GlcNAc) is the fundamental amino sugar moiety that is essential for protein glycosylation. UDP-GlcNAc, an active form of GlcNAc, is synthesized through the hexosamine biosynthetic pathway (HBP). Arabidopsis N-acetylglucosamine-1-P uridylyltransferases (GlcNAc1pUTs), encoded by GlcNA.UTs, catalyze the last step in the HBP pathway, but their biochemical and molecular functions are less clear. In this study, the GlcNA.UT1 expression was knocked down by the double-stranded RNA interference (ds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 95 publications
1
11
0
Order By: Relevance
“…Defects in N-glycan digestion frequently impact plant development and stress responses, resulting in mortality. The growth improvement of cucumber plants in our study aligned with the findings of Chen et al [54], who reported the exogenous application of GlcNAc conferred tolerance and improved growth of wild-type Arabidopsis seedlings under salt stress conditions. Similarly, Sun et al [55] reported that the GlcNAc treatment enhanced the growth of tomato plants via stimulation of microorganism community structure.…”
Section: Discussionsupporting
confidence: 91%
“…Defects in N-glycan digestion frequently impact plant development and stress responses, resulting in mortality. The growth improvement of cucumber plants in our study aligned with the findings of Chen et al [54], who reported the exogenous application of GlcNAc conferred tolerance and improved growth of wild-type Arabidopsis seedlings under salt stress conditions. Similarly, Sun et al [55] reported that the GlcNAc treatment enhanced the growth of tomato plants via stimulation of microorganism community structure.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the iU1s confer slat hypersensitivity, including delay of seed germination and early seedling establishment, in association with the induction of ABA biosynthesis and its signal networks under salt stress. Furthermore, microarray analysis data support the upregulation of genes involved in ABA (such as NCED3 , ABI5 , and ABCG25 ) and salt stress responses (such as RD29A , RD29B , and DREB2A ) ( Chen et al., 2022 ).…”
Section: Hexosamine Biosynthesis Pathway Enzymesmentioning
confidence: 90%
“…Therefore, the Atgna / lig mutant fails to convert GlcN6-P to GlcNAc-6P; however, exogenous GlcNAc can be catalyzed by AtGNK to form GlcNAc-6-P, which further enters the HBP to produce UDP-GlcNAc. Similarly, wild-type plants (Col-o) produce more UDP-HexNAc (UDP-GlcNAc and UDP-GalNAc) by exogenous GlcNAc under normal and salt-stressed conditions ( Chen et al., 2022 ). The coexistence of HBP and salvage pathways may finetune the homeostasis of UDP-GlcNAc contents in plants in response to nutrient fluctuations and environmental stimuli.…”
Section: Salvage Pathway Of Glcn and Glcnacmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also noteworthy that even a large UDP-GlcNAc dose at around 0.5 mM could only induce partial recovery of PD-L1 glycosylation levels. This is understood that protein glycosylation in tumor cells is largely sustained by the glycolysis activities both in terms of UDP-GlcNAc precursors 20,23,53,54 and metabolite supply 55,56 including ATP and NADPH, both of which are significantly suppressed by the BAY-876-mediated blockade of glucose uptake. This is also supported by the quantitative analysis on the biochemical changes in 2-NBDG-treated 4T1 cells, which revealed a positive correlation between 2-NBDG dosage and F6P/UDP-GlcNAc levels (Fig.…”
Section: Impact Of Dna-pae@bay-876 On 4t1-intrinsic Pd-l1 Glycosylationmentioning
confidence: 99%